1998
DOI: 10.1086/311425
|View full text |Cite
|
Sign up to set email alerts
|

The Radio–to–X-Ray Spectrum of GRB 970508 on 1997 May 21.0 UT

Abstract: We have reconstructed the spectrum of the afterglow of GRB 970508, on May 21.0 UT (12.1 days after the GRB), on the basis of observations spanning the X-ray to radio range. The low-frequency power law index of the spectrum, α = 0.44 ± 0.07 (F ν ∝ ν α ), is in agreement with the expected value α = 1/3 for optically thin synchrotron radiation. The 1.4 GHz emission is self-absorbed. We infer constraints on the break frequecies ν c and ν m on May 21.0 UT from a spectral transition from F ν ∼ ν −0.6 to F ν ∼ ν −1.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
104
1
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 24 publications
20
104
1
1
Order By: Relevance
“…In spite of considerable uncertainties in the spectral slopes deduced from observations (Galama et al 1998a), the results shown in Fig. 3 are satisfactory: the observed crossing of the A complementary analysis to that in the previous paragraph is the study of an AG's optical spectrum at a fixed time at which the injection bend is crossing the observed frequency range, or is nearby.…”
Section: Evidence For An Injection Bendsupporting
confidence: 58%
See 2 more Smart Citations
“…In spite of considerable uncertainties in the spectral slopes deduced from observations (Galama et al 1998a), the results shown in Fig. 3 are satisfactory: the observed crossing of the A complementary analysis to that in the previous paragraph is the study of an AG's optical spectrum at a fixed time at which the injection bend is crossing the observed frequency range, or is nearby.…”
Section: Evidence For An Injection Bendsupporting
confidence: 58%
“…The first column is the bend frequency ν 0 b at t = 0, computed with Eq. (14) and the optical AG parameters Galama et al (1998a). of Table 3 (the density n p is extracted from the measured x ∞ with use of Eq.…”
Section: Evidence For An Injection Bendmentioning
confidence: 99%
See 1 more Smart Citation
“…GRB 970508 was also the Ðrst GRB for which a radio counterpart was detected Galama et al 1998b). The broadband (radio to X-ray) spectrum of the afterglow (Waxman, Kulkarni, & Frail 1998 ;Galama et al 1998a) provided strong support for the synchrotron-emitting shock model for afterglows (see, e.g., Sari, Piran, & Narayan 1998).…”
Section: Introductionmentioning
confidence: 69%
“…Some examples are: GRB 970228: α X = 1.06 ± 0.12 (Costa et al 1997). GRB 970508: α O = 1.12 ± 0.07 (Galama et al 1998c); α X = 1.11 ± 0.06 (Galama et al 1998c). GRB 990123: α O = 1.29 ± 0.23 (Holland et al 1999a).…”
Section: The Distribution Of Fitted Parametersmentioning
confidence: 99%